On becoming a psychosynthesis therapist: an investigation of the process - Manson, Doreen Elizabeth (2009)
This research study is concerned with the motivation of psychotherapists who choose to train in Psychosynthesis. Psychosynthesis sits within the transpersonal school of psychology and is less well known than the mainstream schools of Psychoanalytic, Behavioural and Humanistic psychology. There has been considerable research into the motivation of those who choose a career as a psychotherapist, in general, but none into why someone should be drawn to this Spiritual model.